PENERAPAN PASAL 7 UNDANG-UNDANG NOMOR 56 PRP TAHUN 1960 DALAM PELAKSANAAN GADAI TANAH PERTANIAN DI KECAMATAN TANAH JAMBO AYE KABUPATEN ACEH UTARA - Yusra Y; Yulia Y; Herinawati H (JURNAL ILMIAH MAHASISWA FAKULTAS HUKUM UNIVERSITAS MALIKUSSALEH, 2019)
This study aims to identify and analyze and explain the application of Article 7 of Law No. 56 Prp of 1960 in the implementation of agricultural land mortgages, analyze the obstacles to the application of Article 7 of Law No. 56 Prp of 1960, and analyze the efforts made in overcoming obstacles to the application of Article 7 Law 56 Prp of 1960. The implementation of pawning agricultural land is not in accordance with the provisions of Article 7 of Law Number 56 Prp of 1960, the community keeps pawning by not returning agricultural land to its owner even though it has passed the limit on the use of agricultural land. The method used in this study is an empirical juridical approach, with a qualitative legal research type, the legal source used is through field research. The results of this study indicate that the application of Article 7 of Law Number 56 Prp of 1960 in the implementation of land pawning is not appropriate. Barriers to the implementation of Article 7 of Law No. 56 Prp of 1960 are the public's ignorance of Article 7 of Law No. 56 Prp of 1960, the factor that there is no special implementing qanun that regulates the pawning of agricultural land in Aceh and the factor of low public awareness of the law. Efforts that can be made to overcome these obstacles are adding new regulations regarding the application of Article 7 of Law Number 56 Prp of 1960 in each region the existing implementing qanun, conducting negotiations and mediation. Keywords: Implemention of Pawn, Land.